STUDI PERBANDINGAN SIFAT-SIFAT MINYAK KENANGA DARI BLITAR, BOYOLALI DAN CIREBON - Bambang Wiyono; Mohammad Rosid (Jurnal Penelitian Hasil Hutan, 1989)
The  purpose   of  this  research  is to  compare   the  phvsico-chemical    properties   of  cananga oil from  Blitar,  Boyolali, and  Cirebon  with  the  Indonesian   Insutrial  Standard   requirement.   Cananga oils are obtained   from  the  distiller  in Blitar and  Boyolali   regencies.  The  distilling   method   used  in these  regencies are cohobations.   The distilling  time  was 40  hours in Blitar  and 36  hours  in Boyolali,  whereas,  cananga oil properties   from  Cirebon  was based on the literature.   To find  out the difference   in properties,   the student's t-test   was applied.The  results   indicated   that   colour   (visual),   specific  gravity,   refractive   index,   ester  number,  and  ester  content   of cananga  oils  from   Blitar,  Boyolali,  and  Cirebon  have  met  Indonesian   Industrial  Standard  requirement   (Sll.  0026  -   73), except   for  the ester  number  and ester content   of  cananga oil from  Boyolali.  Based on the ester number,  cananga oil from Cirebon  had  a  better  quality   than  that  of  Blitar or Boyolali.  Cananga oil from  Boyolali  had  the  lowest  quality.  Crushing cananga  flowers   before   distilling,  decreased   the  ester  number,   ester  content,   and  yield   of  the  resulting  oil.   Therefore, the crushing of raw of  the cananga flowers prior  to processing  was found   unnecessary.